2018
DOI: 10.3802/jgo.2018.29.e11
|View full text |Cite
|
Sign up to set email alerts
|

Risk stratification models for para-aortic lymph node metastasis and recurrence in stage IB–IIB cervical cancer

Abstract: ObjectiveTo examine the surgical-pathological predictors of para-aortic lymph node (PAN) metastasis at radical hysterectomy, and for PAN recurrence among women who did not undergo PAN dissection at radical hysterectomy.MethodsThis is a retrospective analysis of a nation-wide cohort study of surgically-treated stage IB–IIB cervical cancer (n=5,620). Multivariate models were used to identify independent surgical-pathological predictors for PAN metastasis/recurrence.ResultsThere were 120 (2.1%) cases of PAN metas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 21 publications
2
36
0
Order By: Relevance
“…The current study validates the results of prior studies in that the presence of malignant cells in pelvic cytology testing at the time of radical hysterectomy is associated with decreased survival in women with early-stage cervical cancer. As prior studies were limited in the sample size (range, 105-448) and the number of malignant peritoneal cytology cases (range, [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27], the findings from our study, which included a larger patient pool, are more reliable for interpretation of the analysis [6][7][8][9][10].…”
Section: Prognostic Significancementioning
confidence: 82%
See 3 more Smart Citations
“…The current study validates the results of prior studies in that the presence of malignant cells in pelvic cytology testing at the time of radical hysterectomy is associated with decreased survival in women with early-stage cervical cancer. As prior studies were limited in the sample size (range, 105-448) and the number of malignant peritoneal cytology cases (range, [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27], the findings from our study, which included a larger patient pool, are more reliable for interpretation of the analysis [6][7][8][9][10].…”
Section: Prognostic Significancementioning
confidence: 82%
“…This is a secondary analysis of a prior nationwide multicenter retrospective study conducted in Japanese Gynecologic Oncology Group (JGOG)-designated institutions [18][19][20][21][22][23][24][25]. The study concept and participation call for this landmark collaborator study was initially announced to all JGOG-designated institutions (182 sites), and 116 (63.7%) of these sites voluntarily participated in this study (JGOG-1072S).…”
Section: Data Sourcementioning
confidence: 99%
See 2 more Smart Citations
“… 10 , 11 Matsuo et al reported that PALN recurrence was seen in 195 (4.2%) cases among 4663 clinically PALN-negative cases at surgery in a retrospective analysis of a Japanese nationwide cohort study of surgically treated stage IB–IIB cervical cancer. 12 …”
Section: Gynecological Cancermentioning
confidence: 99%